Do less‐advantaged students avoid prestigious universities? An applicant‐centred approach to understanding UCAS decision‐making. (8th March 2021) - McGrath, Susan; Rogers, Lynne
Abstract : Less‐advantaged students are under‐represented at prestigious universities, but can we infer that they actively avoid them? This research measured university applicants' knowledge of 115 UK universities. Using card‐sort tasks within an interview format, 56 Year 13 students from different types of 16–19 education described how they chose five courses for their application form. Significant cross‐cohort trends in knowledge and understanding demonstrated the influence of different educational environments, but within‐cohort variation showed that applicant characteristics could over‐ride environmental factors. The only cohort where every student understood relative status was an independent school providing individual, career‐focused guidance. Limited resources in state‐sector schools and colleges necessitated 'opt‐in' models of guidance, meaning that only highly motivated students were well‐informed. When students knew that universities are ranked by national league tables, this informed their decision‐making strategy, but reliance on word‐of‐mouth rather than fact‐based information resulted in some students over‐estimating status and graduate outcomes. A new conceptual framework blending developmental and cognitive psychology explained persistent class‐based progression trends whilst demonstrating how personal agency or educational interventions enabled some less‐advantaged students to enter prestigious universities. There was no evidence that prestigious universities were actively avoided, but some students had insufficient knowledge or understanding to make status‐based distinctions.